Upaya Peningkatan Kualitas Baca Tulis Al-Qur’an Santri TPA di Desa Santapan Timur Kecamatan Kandis-Ogan Ilir - Mgs Nazarudin; Kms Badaruddin; Mgs Zahidal Hakim; Rohliyati Rohliyati; Rohima Maharani; Ibrahim Ibrahim (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
One of the problems we face today is the limited number of lessons, teachers, facilities and learning methods for reading and writing the Quran and little interest of children. Such things happen in the village of Santapan Timur during this period. From the observation that almost all children are more interested in watching TV or playing with smartphones than in learning to read and write the Quran, there are so many children and young people who have never been able to read or write the Quran. .This situation is so alarming that it requires reasonable action by various parties to resolve this matter quickly and accurately. The purpose of this academic paper is to improve the ability of TPA students to read and write the Quran. This activity took place from 25 June 2021 to 31 July 2021 at his residence of Mr Syarnubi as Quran teacher in Santapan Timur village. The result obtained from the activity is that the ability of students to read and write the Quran is still relatively lacking, so there is a need for a correct method of teaching Quran reading and writing. Methods that can be used include adapting a student's preferred method of learning to enhance their ability to absorb lessons. However, after the training was conducted, the students' ability to read and write the Koran improved.